Akurasi Arah Kiblat Masjid Menggunakan Qibla Tracker Di Kecamatan Tamalanrea Kota Makassar - Andi Darmawangsa; Andi Sumardin (Universitas Muslim Indonesia, 2022)
This study examines how the accuracy of the Qibla direction of the mosque is determined using one of the modern tools, namely the Taracker Qibla, combined with qualitative descriptive methods through field research (Field Research), with the object of research matching the Qibla direction of several mosques in Tamalanrea District, Makassar City. The approach in this study uses a sociological synthesis approach. Researchers conducted deductive and inductive analyses of the collected data. Then the main tool used in this research is the Qiblat Tracker tool. Qibla direction determination activities using the sophistication of modern tools such as Sun Compass, GPS, Qiblat Tracker, and Google Earth, nowadays, are no longer new. The results of the study found that there were 2 mosques with significant deviations, namely the Baitul Afiah Mosque at 009° and the Nurul Yaqin Mosque at 018°. The biggest deviation is 018°, so the direction of the destination country is towards an African country, not Mecca.Qibla Direction, Qibla Tracker, Mosque